Chronic lead exposure enhances the sympathoexcitatory response associated with P2X4 receptor in rat stellate ganglia. Issue 6 (19th February 2018) - Zhu, Gaochun; Chen, Zhenying; Dai, Bo; Zheng, Chaoran; Jiang, Huaide; Xu, Yurong; Sheng, Xuan; Guo, Jingjing; Dan, Yu; Liang, Shangdong; Li, Guilin
Abstract: Chronic lead exposure causes peripheral sympathetic nerve stimulation, including increased blood pressure and heart rate. Purinergic receptors are involved in the sympathoexcitatory response induced by myocardial ischemia injury. However, whether P2X4 receptor participates in sympathoexcitatory response induced by chronic lead exposure and the possible mechanisms are still unknown. The aim of this study was to explore the change of the sympathoexcitatory response induced by chronic lead exposure via the P2X4 receptor in the stellate ganglion (SG). Rats were given lead acetate through drinking water freely at doses of 0 g/L (control group), 0.5 g/L (low lead group), and 2 g/L (high lead group) for 1 year. Our results demonstrated that lead exposure caused autonomic nervous dysfunction, including blood pressure and heart rate increased and heart rate variability (HRV) decreased. Western blotting results indicated that after lead exposure, the protein expression levels in the SG of P2X4 receptor, IL‐1β and Cx43 were up‐regulated, the phosphorylation of p38 mitogen‐activated protein kinase (MAPK) was activated. Real‐time PCR results showed that the mRNA expression of P2X4 receptor in the SG was higher in lead exposure group than that in the control group. Double‐labeled immunofluorescence results showed that P2X4 receptor was co‐expressed with glutamine synthetase (GS), the marker of satellite glial cells (SGCs). These changes were positively correlated with the dose of lead exposure. The up‐regulated expression of P2X4 receptor in SGCs of the SG maybe enhance the sympathoexcitatory response induced by chronic lead exposure.